Trichinella spp. infection in European polecats (Mustela putorius Linnaeus, 1758) from Romania - Boros Z. (Sciendo, 2021)
The European polecat (Mustela putorius Linnaeus, 1758) is in decline in Romania, often living near human settlements, from mountains to lowlands. They feed on a wide variety of small animals, including rodents, such as mice or rats. The occurrence of this parasite in polecats from Romania was mentioned only once in 1991, but the parasite species was not confirmed by molecular biology. The study aimed to investigate the occurrence of Trichinella spp. in European polecats from Romania and to identify the parasite species by molecular tools. A total of 75 wild European polecats were examined by trichinoscopy and artificial digestion. A large number of animals were examined because of their wide distribution in Romanian territory and their presence near human settlements. For species determination, the positive muscle samples and the larvae recovered from artificial digestion were collected for DNA isolation and further processed by means of Multiplex PCR.